The role of community of practice (CoP) to ensure teacher development and sense of professionalism: The implication for university teachers - Jeylan Wolyie Hussein (College of education, Bahir Dar University, 2023)
A community of practice (CoP) is a set of people who 'share a concern, a set of problems, or a passion about a topic, who deepen their knowledge and expertise... by interacting on an ongoing basis' (Wenger, McDermott, & Snyder, 2002, p. 4). In the context of this paper, CoP refers to an informal as well as semi-formal aggregation of professionals who have come together to forge collaborative learning situation, which is an important step toward fostering professional effectiveness and improving learners' learning achievement. CoP has long gained importance as a model and strategy for improving teaching quality and for enhancing student learning outcomes. It provides teachers the context to learn and grow together. Studies suggest that there is a positive relationship between CoP, student achievement and teachers' professional satisfaction. CoP involves diverse and interacting professional learning practices and processes. Among the major professional learning practices and processes are collective enquiry and collaborative learning. Membership in CoP is characterized by strong professional and emotional bonds between practitioners and their leaders. This paper discusses the implication of CoP for facilitating professional development and supporting the efforts toward collective capacity building in the university context. The paper addresses institutional, attitudinal and orientational variables that prevent CoP from becoming an effective source of professional growth. Finally, it tries to address what should be done to create and sustain CoP and to enable and empower university teachers to become informed and effective practitioners